PROMOSI PERIKLANAN DIGITAL DALAM FESTIVAL PANEN RAYA NUSANTARA (PARARA) 2021 OLEH TOFFEE EVENTS - Rifani Novie Syachkinah; Djuni Akbar (Program Studi MICE, Jurusan Administrasi Niaga, Politeknik Negeri Jakarta, 2023)
The development of technology turns out to have a very big influence in the world of advertising. This condition can be seen from the shift of traditional advertising towards digital. One of the companies that has used digital advertising is Toffee Events which is a company in the field of digital marketing and also engaged in event management and training. Toffee Events as a digital marketing agency was appointed by the PARARA Festival 2021 to be an event organizer who can help in promoting and implementing the Festival Panen Raya Nusantara (PARARA) 2021. The purpose of this study is to find out the advertising promotion carried out by Toffee Events in the PARARA Festival 2021. This research was conducted using qualitative analysis methods from observational data, interviews and documentation. The results of the study showed that the use of digital advertising media that was carried out managed to attract as many as 4006 participants, when compared to the 2019 PARARA Festival which used conventional advertising media and could only attract less than 1000 participants. This promotion process successfully implements the purpose of advertising, namely providing information and adding value well so that the number of participants who register can increase significantly.